Changes of Emission Sources to Nitrate Aerosols in Beijing After the Clean Air Actions: Evidence From Dual Isotope Compositions. Issue 12 (12th June 2020) - Fan, Mei‐Yi; Zhang, Yan‐Lin; Lin, Yu‐Chi; Cao, Fang; Zhao, Zhu‐Yu; Sun, Yele; Qiu, Yanmei; Fu, Pingqing; Wang, Yuxuan
Abstract: Nitrate (NO3 − ) is a major contributing species to haze formation in Northern China. So far, formation processes and source apportionments of nitrate aerosols during haze pollution have not yet been well understood. In this study, the PM2.5 samples were collected in Beijing from 13 November to 24 December 2018. In addition to water‐soluble ions, oxygen (δ 18 O‐NO3 − ) and nitrogen (δ 15 N‐NO3 − ) isotopes in particulate NO3 − were also determined, in order to investigate the formation pathways and potential sources of NO3 − aerosols. The results showed that NO3 − was a dominant species (43%) of secondary inorganic aerosols during the sampling period. The δ 18 O‐NO3 − and δ 15 N‐NO3 − values averaged at 83.8 ± 13.4 and 11.5 ± 5.0‰, respectively. Combining isotope compositions and Bayesian isotope mixing model, we found that heterogeneous reaction and gas phase oxidation contributed equally to nitrate formation during the sampling period. However, the contribution of heterogeneous processes to nitrate increased from 39% during the clean period to 64% during the haze period. On average, coal combustion, biomass burning, vehicle emissions, and soil emission contributed 50%, 26%, 20%, and 4%, respectively, to nitrate aerosols during the sampling period. Compared to the result in 2013, the significant decrease ( 21%) of relative contribution of coal combustion to nitrate was due to strict reduction of coal consumption in Beijing. Finally, the relative contribution of traffic emissions to nitrate increased from 18% during the clean period to 30% during the haze period, suggesting that control of traffic emissions would be an important way to decrease nitrate concentrations and improve the air quality in Beijing. Key Points: Nitrate aerosols in Beijing during the haze events were mainly produced by hydrolysis of N2 O5 under high humidity conditions The contribution of coal combustion to atmospheric nitrate decreased significantly after clean air actions implemented by Chinese government Strict control of traffic emissions would be an important way to decrease nitrate concentrations and improve the air quality in Beijing